2021
DOI: 10.1186/s12645-021-00088-6
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-activated nano-TiO2 loaded with temozolomide paves the way for resection of chemoresistant glioblastoma multiforme

Abstract: Background Glioblastoma multiforme (GBM) is one of the most daunting issues to modern therapeutics, with a higher mortality rate post-diagnosis. Temozolomide (TMZ) is the only available treatment; however, the frequent resistance leaves the oncologists at a dead end. Therefore, new approaches to circumvent the GBM are highly desired. We have employed TiO2 nanosticks loaded with TMZ as nanomedicine for TMZ-resistant GBM resection in this contribution. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Consequently, it has attracted significant interest due to its ability to generate ROS when exposed to external stimuli. [ 353 ] Similarly, the defect‐induced CuTe 2‐x nanozymes, which are sensitive to near‐infrared (NIR)‐II light, have the potential to create a synergistic effect by combining CDT with PTT. [ 354 ] This approach involves the localized concentration of ROS and an increased temperature to eliminate tumors effectively.…”
Section: Application Of Defect Engineeringmentioning
confidence: 99%
“…Consequently, it has attracted significant interest due to its ability to generate ROS when exposed to external stimuli. [ 353 ] Similarly, the defect‐induced CuTe 2‐x nanozymes, which are sensitive to near‐infrared (NIR)‐II light, have the potential to create a synergistic effect by combining CDT with PTT. [ 354 ] This approach involves the localized concentration of ROS and an increased temperature to eliminate tumors effectively.…”
Section: Application Of Defect Engineeringmentioning
confidence: 99%
“…Herein, sonosensitizers can be divided into three major categories: 1) the small molecule organic semiconductors, extensively used as photosensitizers, including porphyrin derivatives [ 82 , 83 ] and cyanine derivatives [ 84 , 85 ]. 2) the inorganic semiconductors exhibit photocatalytic features, with transition metal oxides such as titanium dioxide (TiO 2 ) NPs [ [86] , [87] , [88] , [89] ], ZnO 2 NPs [ 90 , 91 ], and composite semiconductors doping Au [ 92 ], Ag [ 93 ] and Pt [ 94 ]. 3) the organic-inorganic hybrid ones, such as metal-organic framework (MOF)-derivatives [ 95 , 96 ].…”
Section: Current Landscape Of Sdtmentioning
confidence: 99%
“…Only a considerable increase in drug delivery rate was observed macroscopically. Furthermore, Rehman et al [84] loaded temozolomide (TMZ) onto TiO 2 nanosticks through physical adsorption and established nanomedicines for glioblastoma multiforme (GBM) by using these nanosticks. They revealed that when the BBB is opened by ultrasonic radiation, nanomedicines accumulate and are used more effectively in brain tumors.…”
Section: Ultrasound + Nanomedicinesmentioning
confidence: 99%